2022
DOI: 10.3390/polym14183890
|View full text |Cite
|
Sign up to set email alerts
|

On the Response of a Herschel–Bulkley Fluid Due to a Moving Plate

Abstract: In this paper, we study the boundary-layer flow of a Herschel–Bulkley fluid due to a moving plate; this problem has been experimentally investigated by others, where the fluid was assumed to be Carbopol, which has similar properties to cement. The computational fluid dynamics finite volume method from the open-source toolbox/library OpenFOAM is used on structured quad grids to solve the mass and the linear momentum conservation equations using the solver “overInterDyMFoam” customized with non-Newtonian viscosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Ecient viscosity of the Hershel-Bulkley uid (17) in steady laminar ow can be written as [22] µ ef f = µ 0 8v av h The Hershel-Bulkley model is used for optimization of the long-range pipelines pumping such non-Newtonian uids like oil. This model gives good results for steady [23] and pulsatile [24] blood ow through the curved and stenosed arteries.…”
Section: Viscoplastic Modelsmentioning
confidence: 92%
“…Ecient viscosity of the Hershel-Bulkley uid (17) in steady laminar ow can be written as [22] µ ef f = µ 0 8v av h The Hershel-Bulkley model is used for optimization of the long-range pipelines pumping such non-Newtonian uids like oil. This model gives good results for steady [23] and pulsatile [24] blood ow through the curved and stenosed arteries.…”
Section: Viscoplastic Modelsmentioning
confidence: 92%
“…[428][429][430][431][432][433][434] The consideration of self-healing IHs as a versatile 3D printing ink, though currently seems to be far from trivial still by making an appropriate rheological assessment (proper stress or viscoelasticity) might be capable of it. [436][437][438][439][440][441][442][443] Moreover, the consideration of SHHs toward 3D printing is being hindered concerning its printability (quantitative) aspect and is considered to be a timeconsuming approach. However, to overcome such issues, there is a necessity for an ideal rheological testing (in-line or capillary rheology), to establish a printability efficiency of a hydrogel, followed by its flow pattern via print nozzles and recovery afterward.…”
Section: Self-healing Ihs For 3d (Bio)printingmentioning
confidence: 99%
“…However, to overcome such issues, there is a necessity for an ideal rheological testing (in-line or capillary rheology), to establish a printability efficiency of a hydrogel, followed by its flow pattern via print nozzles and recovery afterward. [436][437][438][439][440][441][442][443] Despite so many hindrances toward the flow ability of hydrogel, numerous studies are being conducted for the printing of biomaterials of significant anisotropy and alignment to facilitate cell growth via controlling the flow rate/pattern during printing. [444,445] Noor et al reported the printing of hearts and personalized cardiac patches through cardiomyocytes, endothelial cells, and extracellular matrix hydrogels obtained via patient biopsy.…”
Section: Self-healing Ihs For 3d (Bio)printingmentioning
confidence: 99%
“…The rheological properties of non-Newtonian fluids are a key research direction in the study of grease rheology [24], and the concept of rheological models has been introduced by researchers to quantitatively describe the flow patterns of greases. The current rheological model that can adequately describe wind turbine spindle bearing grease is the Herschel-Bulkley model, which can accommodate a variety of rheological characteristic curves, including shear stress-shear rate curves, strain scan curves, and viscous temperature curves, etc.…”
Section: Rheological Modelingmentioning
confidence: 99%